Audit Pengelolaan Layanan Teknologi Informasi Berdasarkan ITIL Pada IT Marketing & Trading (M&T) PT. Pertamina (Persero) Marketing Operation Region V Surabaya - Ahmad Faiz Zavier; Haryanto Tanuwijaya; Budi Hermawan (Jurnal Sistem Informasi Universitas Dinamika, 2014)
Abstract: IT Marketing & Trading (M&T) PT. Pertamina (Persero) Marketing Operation Region V Surabaya is part of the operational functions of the Corporate Shared Services (CSS) PT. Pertamina (Persero) in the field of Information Technology (IT). Based on the survey results of the services performed by CSS PT. Pertamina (Persero) in the business units and subsidiaries in 2012, primarily for IT M&T PT. Pertamina (Persero) Marketing Operation Region V Surabaya showed a gap between the perceived to the service user expectations with the value -0.73 and -0.68 in the 1st and 2nd semester of 2012. The survey results showed that the quality of IT service management is sufficient but necessary anticipatory efforts to prevent a worse condition.To identify the factors contributing to the gap between perceived services to the user expectations of IT M&T PT. Pertamina (Persero) Marketing Operation Region V Surabaya, it is necessary to audit the management of IT services based on ITSM standard, namely the Information Technology Infrastructure Library (ITIL). Results of IT service management audits that have been conducted show that the cause of the gap is the management has not fully ensure compliance with service management procedures established by the company. The findings and recommendations of the audit can be used to improve the operational performance of service.